Pengaruh Terapi Menulis Ekspresi Terhadap Kesehatan Mental Remaja di Madrasah Aliyah Muhamadiyah Talawaan Bajo Minahasa Utara - Helly M. Katuuk; Sri Wahyuni; Musnabil Buhang (Universitas Muhammadiyah Manado, 2024)
Writing therapy, which includes various techniques of written expression, has been identified as a potentially effective method for improving mental health. Writing activities, whether in the form of personal journals, creative narratives, or deep reflections, allow individuals to express and process emotions and experiences that may be difficult to articulate verbally. This research aims to determine the effect of expressive writing therapy on mental health among adolescents at MA Muhammadiyah Talawaan Bajo in North Minahasa. This study uses a Quasi-Experimental method with a One Group Pretest-Posttest design. The respondents in this study consisted of 18 individuals, with the sampling method employing total sampling. Data collection was conducted using a questionnaire. The collected data were analyzed using the Paired T Test statistical test with a significance level of alpha (α) ≤ 0.05. From the results of the Paired T Test, a P Value of 0.001 was obtained with a significance level of <0.05, which means that the alternative hypothesis Ha is accepted and the null hypothesis Ho is rejected. The conclusion of this study indicates that there is an influence of expressive writing therapy on the mental health of adolescents at Madrasah Aliyah Muhammadiyah Talawaan Bajo Minahasa Utara. It is hoped that the results of this research can provide knowledge in daily life about maintaining and preserving mental health through expressive writing therapy.